Analisis Faktor Risiko Ketidakpatuhan Penerapan Early Warning Score Terhadap Mortalitas Pasien - Sutrisno, Sutrisno; Pramusinto, Handoyo; Setiyarini, Sri (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2022)
Early Warning Score (EWS) is tool that could be applicated to know the early deterioration of the patient. There are seven criteria/indicator in the EWS, these are temperature, O2 saturation, heart rate, O2 supplement, systolic blood pressure, respiratory rate, consciousness. The ability to know the worsening condition in these seven indicators will help the medical team to give prompt treatment to the patients. Wates General Hospital is one of the hospitals in Indonesia that has carry out the EWS system. There is no research conducted on Early Warning Scores in that hospital. The objective to look at the risk of non-compliance with the implementation of EWS on the patient's mortality rate and to see other risk factors for patient mortality. This is an analytic observational study with a case-control retrospective design. Calculation of samples in the case and control groups with purposive sampling method with a total sample of 328 consisting of 82 cases (mortality) and 246 control groups (no mortality patients). Data analysis bivariate data is analized with statictic chi square test and logistic regression. Results The risk for non-compliance to EWS implementation is significantly affect the patient mortality with p-value score of 0,001 (p<0.05). Other risk factors that significantly affect the patient’s mortality are patient severity level, heart disease, stroke, pneumonia, and sepsis. Compliance with the EWS protocol is statistically significant correlation with patient mortality. Implementing good EWS will help medical tim to know early the patient's condition. patient mortality is significantly affected by non-compliance with EWS implementation.